Age dependence of brain β-amyloid deposition in Down syndrome: An [18F]florbetaben PET study. (3rd February 2015) - Jennings, Danna; Seibyl, John; Sabbagh, Marwan; Lai, Florence; Hopkins, William; Bullich, Santi; Gimenez, Monica; Reininger, Cornelia; Putz, Barbara; Stephens, Andrew; Catafau, Ana M.; Marek, Ken
Abstract : Objective: To investigate brain β-amyloid binding in subjects with Down syndrome (DS) using [ 18 F]florbetaben PET imaging. Methods: Thirty-nine subjects with DS (46.3 ± 4.7 years) were assessed with [ 18 F]florbetaben PET imaging. Three blinded independent readers assessed the scans to provide a visual analysis. The primary quantitative imaging outcome was a standardized uptake value ratio (SUVR) obtained for 6 brain regions. Cognitive status was evaluated using the Dementia Screening Questionnaire for Individuals with Intellectual Disabilities (DSQIID). Results: [ 18 F]Florbetaben uptake was correlated with age ( p < 0.0001, R 2 = 0.39); 90% of scans in subjects with DS aged 50 years or older (SUVR = 1.62 ± 0.26), 53% in those aged 45 to 49 years (SUVR = 1.43 ± 0.16), and 7% in those aged 40 to 45 years (SUVR = 1.27 ± 0.11) were visually assessed as positive. Visual and quantitative assessments were highly related (χ 2 = 11.3823, p = 0.0007; Cohen κ = 0.58). Only 2 of 34 participants were considered to have dementia by the DSQIID. Conclusions: Brain β-amyloid binding, as measured by [ 18 F]florbetaben, increases with age in DS. Subjects with DS who have no evidence of dementia demonstrate brain β-amyloid binding in vivo, suggesting that [ 18 F]florbetaben PET imaging may detect β-amyloid in this at-risk population.